Intra-household resource allocation when food prices soar: Impacts on child growth in Indonesia - Yamauchi, Futoshi; Larson, Donald F. (International Food Policy Research Institute, 2019)
An unanticipated spike in food prices can increase malnutrition among the poor with lasting consequences, but parents can protect the most vulnerable within the family by distributing scarce food to minimize adverse impacts. To find evidence of this strategy, we use anthropometric and consumption data from Indonesia, collected before and after the 2007/08 food price crisis. Our results indicate that soaring food prices had a significant and uneven impact on growth among children. Using household fixed effects, we find that the negative impact was significantly larger among larger children, as measured by the initial height z-score. We find that children with low height z-scores at the start of the crisis gained ground relative to their peers during the crisis, consistent with food-resource allocations in their favor. The findings remain robust when controlling for possible differential impacts by gender, family size and food producer status. We conclude that the food price crises had negative long-term impacts on children, and that parental behavior protected the most vulnerable. For Indonesian policy makers, our results indicate that safeguarding family food security should be a priority when targeting specific groups of children is difficult.